Game Poems Videogame Design as Lyric Practice - Magnuson, Jordan (Amherst College Press, 2023)
Scholars, critics, and creators describe certain videogames as being "poetic," yet what that means or why it matters is rarely discussed. In Game Poems: Videogame Design as Lyric Practice, independent game designer Jordan Magnuson explores the convergences between game making and lyric poetry and makes the surprising proposition that videogames can operate as a kind of poetry apart from any reliance on linguistic signs or symbols. This rigorous and accessible short book first examines characteristics of lyric poetry and explores how certain videogames can be appreciated more fully when read in light of the lyric tradition-that is, when read as "game poems." Magnuson then lays groundwork for those wishing to make game poems in practice, providing practical tips and pointers along with tools and resources. Rather than propose a monolithic framework or draw a sharp line between videogame poems and poets and their nonpoetic counterparts, Game Poems brings to light new insights for videogames and for poetry by promoting creative dialogue between disparate fields. The result is a lively account of poetic game-making praxis. "Everyone who loves the true power of games will benefit from the treasure trove of insights in Game Poems." - Jesse Schell, author of The Art of Game Design "Magnuson shines a sensitive and incisive light on small, often moving, videogames." - D. Fox Harrell, Ph.D., Professor of Digital Media, Computing, and Artificial Intelligence, MIT "[Game Poems] tells a new story about games- that games can be lyrical, beautiful, emotionally challenging-to inspire creators and critics alike." -Noah Wardrip-Fruin, author of How Pac-Man Eats "Even as the news swells with impending doom for creativity, writing, and text itself, this literate and crafty book pursues poetry not through implacable algorithms but in concrete and personal play. It should be an indispensable guide for anyone who aims to maintain the true, human promise of technical poetics."-Stuart Moulthrop, coauthor of Twining: Critical and Creative Approaches to Hypertext Narratives "For far too long videogames have flourished - and commanded both capital and attention - in a kind of counterculture that they seem to have created as if ex nihilo for themselves and their players. But we are these players, and their culture has always been integrated with all of our own. In this evenhanded artist-scholar's ars poetica Jordan Magnuson respects the material cultural specificity of videogames while regarding them through the 'lens of poetry' in order to discover - and help create - a practice and an art of Game Poems within the wider field. Magnuson formally, int(erv)entionally embraces this art as lyrically poetic."-John Cayley, Brown University "In Game Poems, Magnuson listens carefully to videogames, and hears them speak to questions of art, language, and meaning that connect our written past to our software future. Read this book and you will hear it too."-Frank Lantz, Director, NYU Game Center "Jordan Magnuson has created a work that ties together the worlds of poetry and videogames in a deep and enlightening way. For those of us who care about the potential of poetic games, Jordan greatly improves the language of how we talk about them and expands our ability to see what this unique form can become. This is one of my favorite books on game design and I apologize in advance to those whom I will end up cornering and not being able to stop talking to about it."-Benjamin Ellinger, Game Design Program Director, DigiPen Institute of Technology "A groundbreaking and accessible book that helps us think about games as poems. With patient tenacity, Magnuson teases out what he felt for years as he engaged in his own practice of making videogames. His mission to help us apply a 'lyric reading' to games so that our engagement with, and appreciation of, games can be enhanced feels deeply personal. Drawing from a wide range of games and computational media scholars, poetry scholars, game creators, and poets, Magnuson provides a rigorous, balanced, and unique interdisciplinary contribution. A must-read for videogame scholars, practicing game makers, and anyone interested in the potential of 'game poems.'"-Susana Ruiz, University of California, Santa Cruz "This book tenaciously wrenches videogame hermeneutics from the insatiable maws of rhetoric and narratology-to the cheers of poets everywhere. In elucidating the lyric characteristics of the ""game poem,"" Magnuson demonstrates not just that poetry is a useful lens for understanding videogames, but also that videogames can be a useful lens for understanding poetry. A rewarding text for scholars, game designers, poets, and anyone in between."-Allison Parrish, Interactive Telecommunications Program and Interactive Media Arts, NYU "A concise, passionate articulation - and defense! - of an artistic space between poems and videogames. If game scholars wish to prove that they are not engaged merely in an apologetics for violent pornography, they need only to teach this book."-Chris Bateman, author of Imaginary Games and 21st Century Game Design "I feel I've found a kindred spirit in Jordan Magnuson and his practical recommendations for creating distilled, compelling, personal videogames - throw out the conventions of game design one at a time? Yes, please! The revelation for me in this book, however, is the heat and power of the language of poets and poetry brought close to videogame design. There's much in here worth pursuing to kindle the fires of new and exciting videogame poems, and Jordan is a capable and delightfully humble guide."-Pippin Barr, author of How to Play a Video Game and The Stuff Games Are Made Of "With Game Poems, Jordan Magnuson lays to rest any last vestige of the notion that the implicit limits of games are as 'entertainment products'. By taking games seriously as successors of the lyric poetry tradition, he opens up new avenues for how game designers can think about what they do, how critical game theorists can approach their many-faceted object of study, and how players can more fully engage with videogames."-Soraya Murray, author of On Video Games "Game Poems shines an important light on a neglected area of videogame theory and provides unique guidance for those interested in exploring the poetic potential of videogames."-Jenova Chen, designer of Flow, Flower, Journey, and Sky: Children of the Light "Popular frameworks for video game scholarship consistently fail to account for the most avant-garde and affective works of interactive art. With Game Poems, Jordan Magnuson provides not only a lens to understand these diverse and important titles but also a guide to constructing the next generation of personal and incisive games. With numerous examples from decades of experimental games, including Magnuson's own minimalist and insightful work, this book is an excellent introduction to the form for neophytes as well as finally providing words to describe a movement that many experienced game poets previously understood only intuitively."-Gregory Avery-Weir, creator of The Majesty of Colors and Looming "Jordan Magnuson is one of a surprisingly small group of artists who see in the technology of videogames a versatile medium capable of expressing much more than conventional games."-Michaël Samyn, co-founder, Tale of Tales; co-creator of Sunset, The Graveyard, and The Path "So much has been written about what games are, and yet there's always a new way of thinking about them. In Jordan Magnuson's Game Poems we discover that games are also a lyrical form of art; that games can be understood as poetry, and that the making games as poetry creates new modes of artistic expression. Jordan Magnuson's book is a fascinating exploration of games as poetry, and the poetry of play."-Miguel Sicart, author of Play Matters, Beyond Choices: The Design of Ethical Gameplay, and Playing Software "In Game Poems, I found a new perspective on the kind of videogames that are dearest to me: short, personal, poetic games. By looking at games through the lens of lyric poetry, Jordan Magnuson puts into focus the workings of that mysterious hodgepodge of audio, visuals, and interactivity: the language of videogames.